Multifocal Neoplastic Involvement of Spleen and Liver with Peritoneal Effusion in a Labrador Retriever: A Case Report - Saikrishna, Kasaraneni Sesha; Matli, Bhargavi; Ahmed, Nasreen; Reddy, Mittapalli Narendra; Meghana, Chinta (Indian Journal of Veterinary Sciences and Biotechnology, 2026)
This case report communicates the findings of multifocal neoplastic involvement of liver and spleen presenting with peritoneal effusion in a Labrador Retriever. A nine year old male Labrador Retriever was presented with exercise intolerance, dyspnea, vomiting, anorexia, weight loss and abdominal distension.